Biological Control of Phytophthora Blight and Anthracnose Disease in Red-pepper Using Bacillus subtilis S54 - Gun Woong Lee; Jong-Chan Chae; Jae Eun Ju; Kui-Jae Lee; Jun Sik Park; Myung Jun Kim; Byoung Yul Soh (Research in Plant Disease, 2011)
Phytophthora blight and anthracnose disease caused by Phytophthora capsici and Collectotrichum gloeosporioides are the most important devastating diseases of red pepper plants, worldwide. Five different bacterial isolates were isolated from the red pepper rhizosphere and non-rhizosphere soil and subsequently tested for antagonistic activity against P. capsisi and C. gloeosporioides. The area of the inhibition zone was taken as a measure for antagonistic activity. Among the 5 isolates tested, S54 exhibited a maximum antagonistic activity under in vitro and in vivo conditions. In greenhouse studies the isolate has successfully reduced the disease symptom. Protect value was 80.8% (Phytophthora blight) and 81.9% (Anthrancnose disease), whereas the infection rate of control plants was 21.3% and 23.2%. Based on the 16S rDNA sequence and API 50CHB Kit analysis the most effective isolate was identified as Bacillus subtilis. The results of the study indicate that the stratin S54 could be used as an potential biological control of Phytophthora blight and anthracnose disease of red pepper.